Children in Self-Care - Millie Ferrer; Anne M. Fugate (EDIS, 2003)
Self-care can be a positive and rewarding experience for children who are ready for it and are properly prepared. It can help them develop independence and learn responsibility. And, it can give them confidence in their own abilities. However, if a child is not mature enough, selfcare can be an anxiety-producing and dangerous situation. This document is FCS2223, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, UF/IFAS Gainesville FL 32611. First published: October, 2003.